2016
DOI: 10.1038/aps.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence: a new therapeutic approach to the treatment of chronic heart failure through SUR2B/Kir6.1 channel in endothelial cells

Abstract: Both iptakalim (Ipt) and natakalim (Nat) activate the SUR2B/Kir6.1 channel, an ATP-sensitive potassium channel (K ATP ) subtype, with high selectivity. In this study we investigated the therapeutic effects of Ipt and Nat against isoproterenol-induced chronic heart failure (ISO-CHF) in rats, and demonstrated a new therapeutic approach to the treatment of CHF through activation of the SUR2B/Kir6.1 channel in endothelial cells. In ISO-CHF rats, oral administration of Nat (1, 3, 9 mg·kg -1 ·d -1 ) or Ipt (3 mg·kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In mice, knockout of endothelial specific Kir6.1 leads to impaired vasorelaxation during hypoxia in the coronary circulation [ 44 ]. In HPAECs, KCOs are capable of reducing endothelial apoptosis, promoting the release of nitrogen oxide and preventing EC dysfunction from ischemia and hypoxia, which could be blocked by K ATP channel blockers [ 9 , 45 , 46 ]. Although the present study showed that K ATP channels played important roles in regulating EC functions, the mouse model with knockout of endothelial specific K ATP channels may be used for further studies to demonstrate the protective effects of K ATP channels on ECs in ALI.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, knockout of endothelial specific Kir6.1 leads to impaired vasorelaxation during hypoxia in the coronary circulation [ 44 ]. In HPAECs, KCOs are capable of reducing endothelial apoptosis, promoting the release of nitrogen oxide and preventing EC dysfunction from ischemia and hypoxia, which could be blocked by K ATP channel blockers [ 9 , 45 , 46 ]. Although the present study showed that K ATP channels played important roles in regulating EC functions, the mouse model with knockout of endothelial specific K ATP channels may be used for further studies to demonstrate the protective effects of K ATP channels on ECs in ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscles expressed Kir6.2/SUR2B [34]. The Kir6.1/SUR2B channel is expressed by endothelial cells [35,36]. Neurons express the Kir6.2/SUR1 channel [21,23,24,37,38].…”
Section: Structure and Expression Of Katp Channelsmentioning
confidence: 99%
“…Iptakalim attenuated cardiac hypertrophy induced by isoproterenol in rats [191]. Nicorandil and natakalim exhibited the same effect in rats receiving isoproterenol [36,192]. Chronic administration of natakalim attenuated cardiac hypertrophy and cardiac failure in rats with permanent CAO [114].…”
Section: Katp Channel Openers and Adverse Cardiac Remodelingmentioning
confidence: 99%
“…For example, testosterone ameliorates vascular aging via the GAS6/AXL signaling pathway ( 79 ). GAS6 signaling is reported to increase NO bioavailability via the androgen receptor-mediated activation of endothelial NO synthase (eNOS) ( 80 ). Testosterone may also function via lncRNA-SWI/SNF complex crosstalk ( 81 ).…”
Section: Epigenetic Mechanisms In Vascular Agingmentioning
confidence: 99%